A short review on the modeling of solid-oxide fuel cells by using computational fluid dynamics: assumptions and boundary conditions - Mohd Nazrul Aman, Nurul Ashikin; Mcuhtar, Andanastuti; Somalu, Mahendra Rao; Rosli, Masli Irwan; Baharuddin, Nurul Akidah; Kalib, Noor Shieela (International Journal of Integrated Engineering, 2018)
Performance tests are vital for the development of solid-oxide fuel cells (SOFCs) and can help determine the potential of developed SOFCs. However, the challenges in performing these tests such as cost, time, and safety limit the development of SOFCs. Computational fluid dynamics (CFD) can be used to numerically predict the performance of developed SOFCs. CFD methods enable the exploration of many design and operational parameters that are difficult to assess experimentally. This paper focuses on the assumptions and boundary conditions used to model the SOFC stack by using a CFD method. Through the discussions, we briefly explain several assumptions that are commonly found in SOFC modeling. These assumptions are important because they can influence the modeling processes and parameters required for simulations. The boundary conditions required for SOFC modeling are then described to provide an overview on how SOFC operations are incorporated into the model and simulations. Our results can help elucidate the significance of assumptions and boundary conditions used in the CFD modeling of SOFCsÂ